دور الأسواق المالية في النمو الاقتصادي في الدول العربية - د. طلال محمود كداوي (PROSPECTIVE RESEARCHES, 2023)
It is expected from stock markets to play a positive role in the process of economic development, specially after capturing the role of commercial banks in financial mediation. This expected role tempted most developing countries to provide various facilities in order to secure the appropriate environment for these markets to exist. Thus, Arab countries witnessed the birth of such markets in their economies. On the contrary to expectation, the statistical analysis revealed the falsity of these markets in promoting economic growth in Arab region. In fact, these markets are not but a speculation club or a place to wash money and facilitate the imposed structural changes.